2019
DOI: 10.1021/acssynbio.9b00118
|View full text |Cite
|
Sign up to set email alerts
|

FadR-Based Biosensor-Assisted Screening for Genes Enhancing Fatty Acyl-CoA Pools in Saccharomyces cerevisiae

Abstract: Fatty acid-derived compounds have a range of industrial applications, from chemical building blocks to biofuels. Due to the highly dynamic nature of fatty acid metabolism, it is difficult to identify genes modulating fatty acyl-CoA levels using a rational approach. Metabolite biosensors can be used to screen genes from large-scale libraries in vivo in a high throughput manner. Here, a fatty acyl-CoA sensor based on the transcription factor FadR from Escherichia coli was established in Saccharomyces cerevisiae … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 70 publications
1
36
0
Order By: Relevance
“…This is likely due to the lower OFF state of essential gene expression provided by the PAC control circuit founded on the minimal PcaO-containing CYC1 promoter, highlighting the importance of biosensor output tuning when coupled to growth-based selection. Moreover, since many repressor-type biosensors established in S. cerevisiae rely on reporters with strong promoters to provide a readable output (Ambri et al, 2020;Dabirian et al, 2019;David et al, 2016;Hector and Mertens, 2017), this issue is believed to be a common concern for future strain stability efforts employing transcriptional repressors. Indeed, even though both types of control circuits lead to an increase in transcription in the presence of the ligand, inactivating mutations in the control circuits will lead to different outcomes depending on the aTF mode-of-action (D'Ambrosio and Jensen, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…This is likely due to the lower OFF state of essential gene expression provided by the PAC control circuit founded on the minimal PcaO-containing CYC1 promoter, highlighting the importance of biosensor output tuning when coupled to growth-based selection. Moreover, since many repressor-type biosensors established in S. cerevisiae rely on reporters with strong promoters to provide a readable output (Ambri et al, 2020;Dabirian et al, 2019;David et al, 2016;Hector and Mertens, 2017), this issue is believed to be a common concern for future strain stability efforts employing transcriptional repressors. Indeed, even though both types of control circuits lead to an increase in transcription in the presence of the ligand, inactivating mutations in the control circuits will lead to different outcomes depending on the aTF mode-of-action (D'Ambrosio and Jensen, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…129 Lastly, the physicochemical stability of DNA can be used to detect natural products such as biotin, vitamin D, and folate at nanomolar levels by strand displacement reactionbased biosensors, which have been shown to exhibit increased sensitivity, low interference, and high controllability. 130,131 The application of (small-molecule) biosensors and the development and engineering of new sensory devices is certainly of interest for different industries to meet performance criteria through the directed evolution of enzymes, 132,133 for the optimisation of microbial cell factories, [134][135][136] and the real-time monitoring of the production of target molecules 137 including (aromatic) alcohols, aldehydes, and acids, 112,113,[138][139][140][141] precursors for the synthesis fatty acids and their derivatives, 84,92,93,[142][143][144][145][146][147][148] isoprene and terpenoids, 149,150 steroids, as well as flavonoids. Biosensor systems for the last two will be highlighted in the following.…”
Section: Biosensorsmentioning
confidence: 99%
“…Due to the lack of techniques available for monitoring fatty acyl-CoA levels in vivo, historically it has been very challenging to design rational approaches to identifying genes that modulate the production of these compounds. Recently, a FadR-based biosensor was developed to screen for S. cerevisiae genes that increase the fatty acyl-CoA pool using FACS (Dabirian et al, 2019b). Using this biosensor, this group found that the overexpression of GGA2 could increase fatty acid levels by 30 and 24% at 8 and 24 h after inoculation, respectively, which was mainly due to a significant increase in the C 16:1 and C 16:0 fatty acid levels.…”
Section: Fatty Acid (Fa)mentioning
confidence: 99%